Atypical Diffusion-Restricted Lesion in 5-Fluorouracil Encephalopathy - Lee, W.-W. (AJNR Am J Neuroradiol, 2012)
Central nervous system toxicity of 5-FU could show various manifestations, such as decreased alertness, disorientation, and agitation. It is generally accepted that lesions of 5-FU encephalopathy are mainly in the deep cerebral white matter and corpus callosum on MR imaging. Here we describe a case of 5-FU encephalopathy in gastric cancer with an atypical reversible diffusion-restricted lesion on MR imaging, showing bilateral basal ganglia, thalami, and parasagittal frontal cortex involvement on diffusion and T2-weighted imaging.